2021
DOI: 10.3390/rs13152870
|View full text |Cite
|
Sign up to set email alerts
|

Unoccupied Aircraft Systems (UASs) Reveal the Morphological Changes at Stromboli Volcano (Italy) before, between, and after the 3 July and 28 August 2019 Paroxysmal Eruptions

Abstract: In July and August 2019, two paroxysmal eruptions dramatically changed the morphology of the crater terrace that hosts the active vents of Stromboli volcano (Italy). Here, we document these morphological changes, by using 2259 UAS-derived photographs from eight surveys and Structure-from-Motion (SfM) photogrammetric techniques, resulting in 3D point clouds, orthomosaics, and digital surface models (DSMs) with resolution ranging from 8.1 to 12.4 cm/pixel. We focus on the morphological evolution of volcanic feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…The crater terrace is located at ~750 m elevation in the uppermost part of the SdF collapse depression (Figure 1B) and comprises three crater zones (Figure 1C): the NE crater zone (NEC), the central crater zone (CC), and the SW crater zone (SWC). Although the crater zones have been remarkably constant in position for more than a century (Washington, 1917;Rittmann 1931;Harris and Ripepe, 2007), they contain a variable number of active vents (Figure 1C) as a function of magma level within the conduit (Spampinato et al, 2008) and of the intensity of the eruptive activity (Civico et al, 2021). It is now recognized that any increase in magma level within the shallow feeder conduit results in an increasing number of explosion quakes (Martini et al, 2007), in a greater seismic tremor amplitude (Ripepe et al, 2009), in a greater number of explosions per hour detected from the monitoring thermal cameras (Calvari et al, 2010) and higher heat flux detected from satellites (Coppola et al, 2012;Corradino et al, 2021a;Ganci et al, 2021), in the inflation of the summit cone revealed by the GBInSAR devices (Di Traglia et al, 2018), and, in general, in morphology changes sometimes related to the shifting of the degassing activity and thermal anomaly within the crater terrace (Marotta et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The crater terrace is located at ~750 m elevation in the uppermost part of the SdF collapse depression (Figure 1B) and comprises three crater zones (Figure 1C): the NE crater zone (NEC), the central crater zone (CC), and the SW crater zone (SWC). Although the crater zones have been remarkably constant in position for more than a century (Washington, 1917;Rittmann 1931;Harris and Ripepe, 2007), they contain a variable number of active vents (Figure 1C) as a function of magma level within the conduit (Spampinato et al, 2008) and of the intensity of the eruptive activity (Civico et al, 2021). It is now recognized that any increase in magma level within the shallow feeder conduit results in an increasing number of explosion quakes (Martini et al, 2007), in a greater seismic tremor amplitude (Ripepe et al, 2009), in a greater number of explosions per hour detected from the monitoring thermal cameras (Calvari et al, 2010) and higher heat flux detected from satellites (Coppola et al, 2012;Corradino et al, 2021a;Ganci et al, 2021), in the inflation of the summit cone revealed by the GBInSAR devices (Di Traglia et al, 2018), and, in general, in morphology changes sometimes related to the shifting of the degassing activity and thermal anomaly within the crater terrace (Marotta et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Since the end of the 2007 flank eruption (Patané et al, 2007;Neri and Lanzafame 2009), the summit crater terrace depression grew mainly on its NE margin building up a thick talus by accumulation of debris, spatter and ejecta erupted during the persistent explosive activity by the NEC vents (Harris and Ripepe, 2007;Di Traglia et al, 2020;Schmid et al, 2021;Tioukov et al, 2022). This rapidly grown constructional morphology is also frequently affected by small collapses (~10 4 -10 5 m 3 ; Falsaperla et al, 2006;Civico et al, 2021). These collapses can be triggered by: 1) dike intrusion and magma fingering in between the loose breccia comprising the cinder cone (Acocella and Tibaldi, 2005;Calvari et al, 2016); 2) magmastatic pressure increase when the magma level within the conduit increases (Di Traglia et al, 2018); or 3) by powerful major explosions such as the 16 November 2020 event (Calvari et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Watts et al (2002) combined photographs and video recordings with theodolite and electronic distance measurements to describe the chronological evolution of the lava dome at Soufrière Hills volcano (Montserrat) throughout the first episode of dome growth (November 1995to March 1998. More recent studies have used photogrammetry to constrain the geometry of an active vent (Dürig et al 2015a) or to investigate lava flow extrusion (Carr et al 2019), flank deformation and stability (Baldi et al 2008;Saito et al 2018), morphological changes in the crater area (Civico et al 2021;Schmid et al 2021), as well as lava dome growth (Johnson et al 2008;Major et al 2008;Schilling et al 2008;Diefenbach et al 2012Diefenbach et al , 2013Walter et al 2013;Salzer et al 2016;Zorn et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Stromboli volcano has been subject of several successfully conducted sUAV monitoring and sampling applications (e.g. Turner et al, 2016;Turner et al, 2017;Rüdiger et al, 2018;Stix et al, 2018;Kueppers et al, 2019;Wakeford et al, 2019;Pering et al, 2020;Civico et al, 2021;Schmid et al, 2021). These missions operated the sUAVs in proximity of the active vents, hence a certain probability of failure caused by environmental conditions and volcanic activity was not to be excluded.…”
Section: Introductionmentioning
confidence: 99%